2000
DOI: 10.1176/jnp.12.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Symptoms and Motoric Subtype of Delirium

Abstract: For 46 patients with delirium who were consecutive referrals to a consultation-liaison psychiatry service, the authors describe the relationships between symptoms, as rated on the Delirium Rating Scale, and delirium motoric subtypes, as defined by Liptzin and Levkoff's criteria. Most cases were of the mixed subtype (46%), 24% were hypoactive, and 30% were hyperactive. Overall scores differed significantly among motoric subtype groups, being highest in the hyperactive, lowest in the hypoactive, and intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
138
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(153 citation statements)
references
References 21 publications
9
138
0
6
Order By: Relevance
“…Other studies have also found mixed subtype as the most common. 23,24 It has been suggested that the subtypes differ in the underlying pathology, response to therapeutic intervention and outcome, with hypoactive delirium having a notably poorer prognosis although some studies have not found such an association. 25,26 Hypoactive delirium is likely to go undiagnosed thereby resulting in poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found mixed subtype as the most common. 23,24 It has been suggested that the subtypes differ in the underlying pathology, response to therapeutic intervention and outcome, with hypoactive delirium having a notably poorer prognosis although some studies have not found such an association. 25,26 Hypoactive delirium is likely to go undiagnosed thereby resulting in poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These include unawareness of the environment, lethargy, apathy, decreased level of alertness, psychomotor retardation, decreased speech production, and episodes of unresponsiveness or staring. Patients with hypoactive delirium often endorse depressive symptoms, such as low mood (60%), worthlessness (68%), and frequent thoughts of death (52%) [30]. Regarding our study, hyperactive delirium was the most common subtype, accounting for 81% of total cases of delirium.…”
Section: Discussionmentioning
confidence: 44%
“…Others have confirmed the presence of these motoric subtypes. According to these studies, there are at least three types of delirium based on their clinical manifestations: hyperactive, hypoactive, and mixed [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Delirium in this context is referred to as hypoactive delirium, and is characterised by decreased mental and physical activity and inattention. 16 Physicians and nurses frequently overlook this quiet or hypoactive delirium. Features also include lethargy, confusion and sedation.…”
Section: Subtypes Of Deliriummentioning
confidence: 99%